2016
DOI: 10.5501/wjv.v5.i4.144
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Wnt/β-catenin signaling by herpesviruses

Abstract: The Wnt/β-catenin signaling pathway is instrumental in successful differentiation and proliferation of mammalian cells. It is therefore not surprising that the herpesvirus family has developed mechanisms to interact with and manipulate this pathway. Successful coexistence with the host requires that herpesviruses establish a lifelong infection that includes periods of latency and reactivation or persistence. Many herpesviruses establish latency in progenitor cells and viral reactivation is linked to host-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 81 publications
(86 reference statements)
0
21
0
Order By: Relevance
“…Numerous protein interactions and regulators of β-catenin have been characterized, with one known transcriptional co-activator being CBP for DNA binding. The association between this prosurvival factor and infection remains understudied as only a small number of studies exist linking HSV-1 or other viral infection to β-catenin activation (42)(43)(44). In this study, we show that multiple commercially available compounds targeting CREB and β-catenin systems demonstrate antiviral efficacy against HSV-1.…”
Section: Discussionmentioning
confidence: 74%
“…Numerous protein interactions and regulators of β-catenin have been characterized, with one known transcriptional co-activator being CBP for DNA binding. The association between this prosurvival factor and infection remains understudied as only a small number of studies exist linking HSV-1 or other viral infection to β-catenin activation (42)(43)(44). In this study, we show that multiple commercially available compounds targeting CREB and β-catenin systems demonstrate antiviral efficacy against HSV-1.…”
Section: Discussionmentioning
confidence: 74%
“… 18 Numerous studies have suggested the important functions of Wnt/ β -catenin signaling in several cancers. 19 In the absence of Wnt stimulation, β -catenin is phosphorylated by a destruction complex consisting of GSK3 β , CK1, Axin1, Axin2 and APC, resulting in the β -catenin degradation. Upon binding of Wnt, phosphorylation of β -catenin is blocked and allows β -catenin to dissociate from the destruction complex.…”
mentioning
confidence: 99%
“…Then, β -catenin accumulates in cytoplasm that results in translocation of β -catenin to the nucleus and interacts with TCF/LEF to transactivate the downstream target genes including Cyclin D1, c-Myc, CD44 and ALDH etc . 19 , 20 Wnt/ β -catenin signaling pathway is an important inducer of EMT and critical for the maintenance of CSCs. Upon activation by specific ligands, β -catenin is released from the membrane and promotes transcription of genes involved in mesenchymal phenotype induction and the maintenance of CSCs.…”
mentioning
confidence: 99%
“…In going forward, WNT is an important signaling pathway to consider in CMV latency as it is critical to the control of latency in other herpesviruses. Herpesviruses typically inhibit WNT signaling during replication and promote WNT signaling for the establishment of latency (Reviewed in [ 141 ]). Both EBV and KHSV target Glycogen synthase kinase 3 α/β (GSK-3) of the WNT destruction complex to prevent the degradation of β-catenin during latency [ 142 , 143 , 144 ].…”
Section: Cmv-mediated Control Of Host Signaling For Latency/reactimentioning
confidence: 99%